Roar! - Irwin, Bindi, 1998- (Bindi wildlife adventures, 2011)
Bindi, Robert and Terri Irwin are on their way to Sumatra to collect three gorgeous tiger cubs to take back to the Australia Zoo. Soon after they are introduced to the mischievous trio, Bindi and her new friend Madi get involved in tracking down a gang of dangerous tiger poachers.